Glutamine supplementation affected the gut bacterial community and fermentation leading to improved nutrient digestibility in growth-retarded yaks. Issue 7 (16th June 2021) - Ma, Jian; Zhu, Yixiao; Wang, Zhisheng; Yu, Xiong; Hu, Rui; Wang, Xueying; Cao, Guang; Zou, Huawei; Shah, Ali Mujtaba; Peng, Quanhui; Xue, Bai; Wang, Lizhi; et al.
ABSTRACT: This study evaluated the effects of glutamine supplementation on nutrient digestibility, immunity, digestive enzyme activity, gut bacterial community and fermentation of growth-retarded yaks. A total of 16 growth-retarded yaks were randomly allocated to two groups: negative control (GRY) and glutamine supplementation group (GLN). Another eight growth-normal yaks were used as a positive control (GNY). Compared with GRY group, the crude protein digestibility was higher in GLN and GNY animals and the neutral detergent fiber digestibility was increased in GLN yaks. The concentrations of serum IgA, IgG, IgM and IL-10, as well as butyrate concentration and cellulase activity in the rumen and cecum were higher in GLN yaks compared to those in GRY animals. Supplementation with glutamine enhanced the chymotrypsin activity and increased the relative abundances of unclassified Peptostreptococcaceae and Romboutsia while decreased the relative abundances of unclassified Chitinophagaceae and Bacteroides in the jejunum and ileum of growth-retarded yaks. In the cecum, the relative abundance of unclassified Muribaculaceae was higher in GLN group than that in GRY group. The findings in this study suggest that the improved nutrient digestibility and immunity of growth-retarded yaks with glutamine supplementation may be through its potential impact on the lower gut host and microbial functions. Abstract : Regulation of gastrointestinal bacterial community by dietary glutamine supplementation may improve the gastrointestinal fermentation, digestive enzyme activity, nutrient digestibility and immunity of growth-retarded yaks.